Klasifikasi Algoritma C4.5 Dalam Penerapan Tingkat Kepuasan Siswa Terhadap Media Pembelajaran Online - Kiki Aidi Saputra; Jaya Tata Hardinata; Muhammad Ridwan Lubis; Sundari Retno Andani; Ilham Syahputra Saragih (STMIK Budi Darma, 2020)
This study aims to determine the effect of the level of student satisfaction on online learning media This study aims to determine the effect of the level of student satisfaction on online learning media in SMA YPI Swata Dharma Budi. Internet media has an important role to learn for students. This research population applies the C4.5 Algorithm in applying the level of student satisfaction to online learning media. This type of research is the classification with the concept of data mining involving as many as 100 student data in SMA YPI Swasta Dharma Budi which is categorized by: Satisfied and Dissatisfied. In collecting data using a questionnaire and the variables used in this study there were four namely interest in learning, ways of learning, learning, learning media. The method used in this study is the classification method. After manual calculation, verification is carried out using the RapidMiner application. Tests conducted with the Rapidminer software using the apply model and% performance obtained value of 86.67% accuracy.